Yield and Fiber Quality Balance in Upland Cotton (Gossypium Hirsutum L.) Breeding (Bangladesh Journal of Botany, 2023)
The main aim of cotton breeding is to combine yield and fiber quality by broadening the genetic base of the genotypes. The performance of multi-parent hybrid populations and the association among yield attributes and quality parameters were investigated by biometrical techniques, i.e., principal component analysis (PCA), correlation analysis and decision tree. The mean and range of crosses were higher for seed cotton yield and ginning out-turn; similar for fiber strength and length; coarse for fiber fineness compared to their parents. Significantly negative correlations were recorded between seed cotton yield and fiber length; ginning out-turn and fiber fineness. PCA analysis indicated that fiber fineness and ginning out-turn were on the same platform, whereas seed cotton yield per plant with fiber length and fiber fineness were on opposite platforms. The decision tree model showed that fiber fineness (4.60 mic.) within commercial limits depends on the optimization of seed cotton yield per plant of approximately 54.27 g and ginning out-turn of 42.60% in single plant selection.Bangladesh J. Bot. 52(2): 283-290, 2023 (June)